Design of a methodology for logistical intervention of agrifood supply chains (2018)
The agriculture is one of the most important economic sectors for Colombia's economic. It is important to recognize those elements that allow regions to differentiate among themselves. Tolima has well defined logistics and agribusiness as two strategic areas for its economic and social development in 2025. These sectors have the necessity to developed tools that allow prioritizing the products that must be selected and intervened. Once products has been selected, tools must be developed to prioritize the strategies to be implemented for their improvement and at the same time to determine the organizations that can be articulated, so that the implementation of the strategies has a greater impact. This work develop a methodology for the prioritization of agricultural products taking into account qualitative and quantitative variables through the application of decision theory techniques. It involves a conceptual framework that include socio-economical, technical, technological, political, and environmental factors. Unlike existing methodologies, this methodology allows classifying of products according to their development level to implement effective strategies. This work also develop a methodology for prioritizing of improvement strategies that involves important aspects related to making decision. The methodology takes into account the capacity to evaluate the impact that the implementation of the strategies would have on the problems present in a supply chain, and it was developed as an adaptation of the Quality Function Deployment methodology. Finally, a new agrifood supply chain organization for Tolima's chains was proposed. Their effects were evaluated with a simulation model based on dynamic systems approach. The results were used into the project: Design and implementation of a logistic model for value integration in horticultural chain of Tolima", whose aim was to improve logistics management and operation in fruit and vegetable chains of Tolima."--Tomado del Formato de Documento de Grado